A New Reliable Switched-Capacitor-Based High Step-Up Five-Level Inverter - Milad Ghavipanjeh Marangalu; Naser Vosoughi Kurdkandi; Kourosh Khalaj Monfared; Yousef Neyshabouri; Hani Vahedi (IEEE Open Journal of the Industrial Electronics Society)
This article presents a new transformerless switched-capacitor (SC) based five-level grid-connected inverter with inherent voltage-boosting capability. The proposed topology achieves a voltage gain factor of two without requiring an additional dc–dc boost converter or transformer, resulting in a more compact, cost-effective, and efficient design. A single SC cell is utilized to perform bidirectional capacitor charging during both positive and negative grid half cycles, thereby improving energy transfer efficiency and significantly reducing capacitor size and volume compared with the conventional topologies. The inverter employs a minimal number of components—only nine switches and one flying capacitor—while maintaining high performance. Only five switches operate at high frequency, which reduces switching losses, gate driver complexity, and electromagnetic interference. A straightforward control strategy ensures that the inverter delivers a high-quality sinusoidal current waveform to the grid and supports both active and reactive-power flow under various power factor conditions. The reliability of the proposed inverter is analyzed, and its performance is validated through detailed simulations and experimental results. A comparative study with the existing solutions highlights the advantages of the proposed topology in terms of efficiency, voltage gain, component count, and waveform quality.